A Study of Monthly Precipitation Timeseries from Argentina (Corrientes, Córdoba, Buenos Aires, and Bahía Blanca) for the Period of 1860–2023 - Canziani, Pablo O. (2025)
Fil: Canziani, Pablo O. Universidad Tecnológica Nacional; Argentina